Compatibility Polymorphism Based on Long-Term Host-Parasite Relationships: Cross Talking Between Biomphalaria glabrata and the Trematode Schistosoma mansoni From Endemic Areas in Brazil - Lima, Mariana G.; Montresor, Lângia C.; Pontes, Joana; Augusto, Ronaldo de C.; Silva, Jairo Pinheiro da; Thiengo, Silvana C. (Frontiers in Immunology, 2019)
Sympatric snail populations have been kept in the laboratory since the isolation of the parasite from the field. To evaluate the influence of the intermediate host in the infectivity of S. mansoni, this allopatric strain was compared to two sympatric strains, from different geographical origins, and with different time of maintenance in the laboratory. Snail–trematode compatibility was accessed for a total of 9 possible combinations (3 snail populations, 3 schistosome strains), using different charges of parasite: 1, 5, 10 and 15 miracidia/snail. Each S. mansoni strain was characterized according to its infectivity phenotype that reflects the efficiency of their infection mechanism and all B. glabrata populations were characterized according to its (in)compatible phenotype that reflects the level of (un)susceptibility they display. For all host-parasite combinations tested the dose-response relation indicated a trend for an increase in the infectivity of S. mansoni when higher miracidial doses were used. SmRES-2 presented the highest overall infectivity rate, especially in the SmRES-2/BgRES interaction with 15 miracidia/snail. However, SmRES was more infective to BgBAR than SmRES-2, indicating that SmRES strain was more infective at the first contact with this new host than after 2 years of interaction (SmRES-2). BgBAR presented the highest susceptibility to infection. SmRES and SmRES-2 are the same parasite strains. It seems that during these 2 years of interaction, BgBAR acted like a filter and shifted the compatibility polymorphism of the strain SmRES. SmRES-2 became more infective to BgRES (sympatric) than to BgBAR (allopatric), and conversely, SmRES was more infective to BgBAR (allopatric) than to BgRES (sympatric). This interplay suggests that epigenetic mechanisms are prompting these changes. This study concerns with infection of B. glabrata snails from different Brazilian localities with S. mansoni in allopatric and sympatric associations that will partially help in understanding the natural epidemiology of schistosomiasis within natural snail populations in watercourses. This work demonstrates that there is a shift on the compatibility polymorphism profile resulting from sympatric and allopatric interactions of B. glabrata and S. mansoni that constantly change during the time of interaction.